The seagull [videorecording (DVD)] - Moss, Elisabeth, 1982-; Ronan, Saoirse, 1994-; Bening, Annette; Chekhov, Anton Pavlovich, 1860-1904 (Sony Pictures Classics, 2018)
In the early twentieth century, an aging actress and her lover visit the estate of her elderly brother.